PERSEPSI PARA PIHAK TERHADAP KEARIFAN LOKAL MASYARAKAT DALAM MELESTARIKAN HUTAN DI KENEGERIAN ROKAN KECAMATAN ROKAN IV KOTO KABUPATEN ROKAN HULU - Mawaddatun ‘Izzati; M. Mardhiansyah; Evi Sribudiani (Jurnal Ilmu Ilmu Kehutanan, 2022)
Local wisdom is useful as life knowledge and also as human behavior in preserving the environment. Preservation of forests in local wisdom has declined, like in Kenegerian Rokan, the existence of forest was decreasing. The purpose of this reserach was to describe the perceptions of various parties towards the local wisdom of the Rokan community to preserve forests in Kenegerian Rokan. This research used purposive sampling method which has ten responden and used qualitative descriptive to analyzed the result. The results showed that local wisdom was not well maintained and no longer valid. Community figures in Kenegerian Rokan were traditional leaders, religious leaders and educational figures, that all of them are “Ninik Mamak”. Many community figures were concerned with their own interests and impose weak sanctions, made people did not care about each other and cause a lot of conflicts. It has led the communities mistrust of “Ninik Mamak” and caused communities no longer maintain and preserve the forest.